2004
DOI: 10.1074/jbc.m312638200
|View full text |Cite
|
Sign up to set email alerts
|

Dual Functions of Transcription Factors, Transforming Growth Factor-β-inducible Early Gene (TIEG)2 and Sp3, Are Mediated by CACCC Element and Sp1 Sites of Human Monoamine Oxidase (MAO) B Gene

Abstract: Monoamine oxidases (MAO)A and B catalyze the oxidative deamination of many biogenic and dietary amines. Abnormal expression of MAO has been implicated in several psychiatric and neurodegenerative disorders. Human MAO B core promoter (؊246 to ؊99 region) consists of CACCC element flanked by two clusters of overlapping Sp1 sites. Here, we show that cotransfection with transforming growth factor (TGF)-␤-inducible early gene (TIEG)2 increased MAO B gene expression at promoter, mRNA, protein, and catalytic activity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
91
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 64 publications
(93 citation statements)
references
References 32 publications
1
91
1
Order By: Relevance
“…Inhibition of insulin gene expression by KLF11 overexpression, glucose-induced insulin secretion and regulation of endogenous KLF11 mRNA expression by glucose Although a dosedependent KLF11 overexpression-induced increase in MAOB mRNA levels was described in both SH-SY5Y and HepG2 cells [12], we did not observe significant regulation of MAOB gene expression in INS-1E beta cells (not shown). However, qPCR analysis revealed that hKLF11 overexpression significantly reduced Ins2 gene expression while Ins1 mRNA levels remained unaffected (Fig.…”
Section: Resultscontrasting
confidence: 56%
See 1 more Smart Citation
“…Inhibition of insulin gene expression by KLF11 overexpression, glucose-induced insulin secretion and regulation of endogenous KLF11 mRNA expression by glucose Although a dosedependent KLF11 overexpression-induced increase in MAOB mRNA levels was described in both SH-SY5Y and HepG2 cells [12], we did not observe significant regulation of MAOB gene expression in INS-1E beta cells (not shown). However, qPCR analysis revealed that hKLF11 overexpression significantly reduced Ins2 gene expression while Ins1 mRNA levels remained unaffected (Fig.…”
Section: Resultscontrasting
confidence: 56%
“…However, KLF11 seems to be expendable for globin gene expression since KLF11 −/− mice display normal haematopoiesis at all stages of development [18]. Interestingly, Ou et al [12] confirmed binding of KLF11 to both Sp1/GC and CACCC sites, thereby influencing the human MAOB promoter as an activator via its Sp1/ GC site or as a repressor via its CACCC site. In contrast, we could not detect binding of in vitro translated hKLF11 to the CACCC box sequence within hInsP.…”
Section: Discussionmentioning
confidence: 99%
“…In generating the R1-stable cell line, SK-N-BE(2)-C cells were plated at a density of 5 ϫ 10 6 cells in a 10-cm dish. The next day the R1 expression vector or pcDNA3.1 was transfected into cells with a superfect transfection reagent (25). After 24 h, cells were replated onto 5-cm dishes, and Geneticin (G418; 600 g͞ml) was added.…”
Section: Withdrawal Of Growth Factors (Serum Starvation) and Treatmentsmentioning
confidence: 99%
“…The real-time PCR was performed with a SYBR supermix kit (Bio-Rad), and the GAPDH mRNA primer was included in every plate to avoid sample variations. A ⌬C T value was then calculated as described (25).…”
Section: Withdrawal Of Growth Factors (Serum Starvation) and Treatmentsmentioning
confidence: 99%
“…The substrate and inhibitor specificities are influenced by a single amino acid (10). The regulations of these two genes are different (11)(12)(13). MAO inhibitors have long been used as antidepressant drugs (14), and MAO B inhibitors are used to treat Parkinson's disease (15).…”
mentioning
confidence: 99%